Material Process in Mechanical Engineering Texts: Systemic Functional Linguistics Perspectives - Mulyati Khorina (Linguistics and ELT Journal, 2020)
A creative clause is a type of clause operating either on the material process of doing or material process of happening. Since both material process types may occur in creative clauses, this study aims to investigate what verbs realize each of material process in creative clauses occurring in Mechanical Engineering texts and what verbs may realize both of the material process types in Mechanical Engineering texts. Therefore, this study employed the Systemic Functional Linguistic (SFL) framework to analyze the qualitative data obtained from an introductory textbook of Mechanical Engineering. The results showed that verbs create, form, make, produce, and develop realize the material process of doing while verbs appear, grow, occur, and develop realize the material process of happening. It implies that only one verb may realize both material process types.